About a finite-difference algorithm of modeling the adsorption kinetic processes - Lyashko, S. I.; Gryshchenko, O.Yu.; Fedorova, V. S.; Zagorodnya, G. O. (Reports of the National Academy of Sciences of Ukraine, 2015)
Physico-chemical or chemical methods of wastewater treatment, while ensuring the quality of water according to the requirements, allow one to obtain valuable products from wastes and to reduce the production losses. Despite the urgency of the problem, no method of mathematical modeling of such processes for the substantiation of rational technological schemes is considered till now. We propose an algorithm and a reasonable numerical simulation of continuous adsorption processes in multidevices. We consider the numerical methods for a mathematical model of the kinetics of adsorption for the urgent problem of post-treatment of industrial effluents. We built actual finite-difference algorithms and proved their stability under a perturbation of the coefficients of equations, which were obtained during the numerical experiment.